Ergonomic behaviour of learners in a digitally driven school environment: Modification using an ergonomic intervention programme - Ingrid V. Sellschop; Hellen Myezwa; Witness Mudzi; Eustatius Musenge (AOSIS, 2018)
Background: Computer use is increasing amongst adolescents and so is the potential for related musculoskeletal pain and postural changes. The cumulative effect of this technology-induced, sedentary lifestyle leads to poor posture, pain, repetitive strain injury and dysfunctional movement patterns. Objectives: The purpose of this study was to establish the effect of a computer-related ergonomic intervention for adolescents in a school environment on posture and ergonomic behaviour. Methods: All Grade 8 learners at two randomly selected private schools in Johannesburg were invited to participate in the study (n = 127). A controlled trial compared an intervention group with a control group. The computer usage questionnaire and rapid upper limb assessment (RULA) were assessed at baseline, 3 and 6 months post-intervention. The intervention consisted of a participatory educational programme. An intention-to-treat analysis was undertaken. Alpha level was set at p = 0.05. Descriptive statistics (frequencies and percentages) and between-group analysis of variance, determined differences in the number of participants in the RULA action levels between groups after the intervention and the comparison of positions and type of computer. Results: At 6 months post-intervention, there were no participants in action level (AL) 4 and the number of participants in AL 3 had reduced from 26.2% at baseline to 14.8% in the intervention group (p < 0.001). The control group RULA scores worsened over the period of 6 months. Although the learners were still not in an 'acceptable' range of postural positions, there was a significant improvement between the pre-intervention and post-intervention stage (p < 0.001). Conclusion: These findings demonstrate the effect of an ergonomic intervention and its sustainability over 6 months. Clinical implications: The clinical contribution of this study to our healthcare system is that through the early identification and intervention of the poor ergonomics in a school environment, a positive impact on reducing poor postural behaviour amongst learners can be achieved.